2018
DOI: 10.1177/0300060517747163
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic dysfunction in sepsis due to severe acute pancreatitis complicated by intra-abdominal hypertension

Abstract: ObjectiveThis study aimed to examine the mechanism of diaphragmatic dysfunction in sepsis due to severe acute pancreatitis (SAP) with intra-abdominal hypertension (IAH) in a rat model.MethodsThe rats were assigned at random to four groups: (1) control (n = 5), (2) SAP (n = 5), (3) SAP+IAH (n = 5), and (4) SAP+IAH+SS-31 (n = 5). Length and force output of the diaphragm were analysed in vivo. Histopathological examinations were performed by haematoxylin–eosin. Oxidative stress levels related to protease in diaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Sepsis declines the activity of oxygen-free radical scavengers in tissues, causing excessive oxygen-free radicals to be accumulated in tissues and can not be removed timely, and excessive oxygen-free radicals can induce lipid peroxidation, and then result in oxidative damage [ 28 ]. SOD and CAT, as antioxidant enzymes, are oxygen-free radical scavengers that present in the body [ 29 ]. MDA is the main product of lipid peroxidation [ 30 ], and a large number of oxygen free radicals in tissues can also activate apoptotic response and induce apoptosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis declines the activity of oxygen-free radical scavengers in tissues, causing excessive oxygen-free radicals to be accumulated in tissues and can not be removed timely, and excessive oxygen-free radicals can induce lipid peroxidation, and then result in oxidative damage [ 28 ]. SOD and CAT, as antioxidant enzymes, are oxygen-free radical scavengers that present in the body [ 29 ]. MDA is the main product of lipid peroxidation [ 30 ], and a large number of oxygen free radicals in tissues can also activate apoptotic response and induce apoptosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Severe acute pancreatitis complicated by IAH/ACS increases the risk for sepsis (Liao et al, 2018). The human intestine contains many microorganisms, and some of these Gram-negative bacteria can produce the toxin LPS.…”
Section: Discussionmentioning
confidence: 99%
“…e antioxidants network consists of enzymes, such as catalase, glutathione peroxidase (GPx), thioredoxin reductases, superoxide dismutase (SOD), and soluble antioxidants such as glutathione and vitamin E [48]. It was found that GPx and SOD levels were significantly lower in the diaphragm of severe acute pancreatitis with intra-abdominal hypertension in a rat model [61]. Protein and mRNA expression levels of CuZnSOD, MnSOD, and GPx were found to be decreased or unaltered in the aged muscle even if its activity was increased [62].…”
Section: Mitochondrial Oxidative Stress In the Development Ofmentioning
confidence: 99%